Emerg?ncia de comunica??o corporal monomodal entre agentes rob?ticos - Jesus, Moab Rodrigues (2018)
Communication is a complex and diversified phenomenon by which information can be shared between different individuals. Its emergence and evolution are not completely understood, remaining as an open study in science. On the other hand, computational modeling of the emergence of communication has contributed to advances in research. Empirical and theoretical studies indicate that gestural communication was the precursor of spoken communication in humans, but the computational modeling of such mode of communication is still incipient. In this work we aim to model the emergence of gestural communication using robots with limited sensory domain, i.e., only monomodal domain, so that the main characteristics involved in the process are evidenced and the emergence process is better understood. We used Evolutionary Robotics and Language Games to model the experimental scenarios and evolution of robots, and performed an analysis of the representation processes involved. Results showed that it is possible to emerge symbolic and iconic communication, even in restricted sensory conditions, as is the case in this work